Association between perceived depression, anxiety and stress with Body Mass Index: results from a community-based cross-sectional survey in Iran (Italian Journal of Public Health, 2011)
Objective: The findings of studies concerning the association between obesity and psychological disordersare conflicting. Some have reported a positive association, some a negative association while some found no association at all. This study aimed to investigate the associations between obesity and perceived depression, anxiety and stress.Methods: This study was a community-based cross-sectional survey conducted from May 2006 to December 2007 in Tehran, Iran. The sample size of 3,000 people (age≥20 years) was determined using a sample size formula and participants were selected by random sampling. Survey participants were asked to state their height and weight as well as answer questions concerning whether they had experienced symptoms of depression, anxiety, and stress in the past six months. Some demographic variables such as sex, age, marital status, education and tobacco smoking habits were included in the analysis.Results: The prevalence of perceived depression, anxiety, and stress were higher in women than in men. A higher proportion of underweight and obesity was observed in women. Being underweight, overweight and obese were associated with a one to four-fold increased risk for perceived depression, anxiety and stress.Conclusions: Abnormal body weight is associated with an increased risk of perceived depression in both men and women. Prospective and experimental studies in large samples are needed to explore possible explanations of the association and the direction of causal association between BMI and psychological disorders.
Keywords: BMI; depression; anxiety; stress; obesity; overweight; Iran